An amazing feather loss: Review - Bárdos, László (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
Beside the regular and some pathologic molt the so called „fright molting" has been known among several species of birds. This feather loss explained as a way of escaping a predator for the surveillance. Some other similar phenomenon in the other species is discussed in the article.